Extracting Profits: State Regulation and the Canadian Ombudsperson for Responsible Enterprise - Kristine Johnston; Steven Bittle (Canadian Journal of Law and Society)
Taking the Canadian Ombudsperson for Responsible Enterprise (CORE) as its focus, this paper critically examines the Canadian government’s efforts to regulate the extractive industry. Using insight from ideology theory and critical discourse analysis, and drawing empirically from Canadian Parliamentary debates, official government and NGO reports, and various news items regarding the development of the CORE, we document how dominant voices prioritized the economy, downplayed the systemic violence of the industry, and redirected blame to “underdeveloped” countries, on route to a regulatory framework that is voluntary and which fails to address the underlying causes of corporate harm and violence. While the CORE represents a “logical” state response to corporate crime, we nevertheless emphasize the importance of ongoing debates about its role in combating corporate impunity. This not only reinforces the idea that (capitalist) dominance is never absolute but signals the ever-present nature of resistance and possibility for change.